Maternal Health Condition and Lying Behavior in Grazing Milk Cows: Comprehensive Analysis - Amita Shukla, Anatha Charan Ojha, Savita (Revista Electronica de Veterinaria, 2024)
Many cows face difficulties during the shift from pregnancy to lactation, which results in a high frequency of postpartum illnesses. There is a significant study vacuum relating the laying habits of pastured milk cows, despite the fact that changes in lying behavior might be a sign of sickness. In order to address these issues, the study describes the lying behavior dairy cows engage in grazing during the first three weeks following calving and investigates the connections across lying behavior and transition illnesses. During winter calving, cows were registered as they calved, and laying behavior was recorded at one-minute intervals using electronic data recorders. Cows were divided into three health categories: healthy, lame, and unwell, diseases were recorded up to 21 days after calving. Individuals in the ill group were subdivided between those, who had one clinical health incident and those who had several. The analysis of lying behavior took into account variables including parity and health state. It is different for primiparous and multiparous dairy cows to lie when they are grazing. More time is spent lying down in multiparous cows than primiparous cows, which have more lying sessions. Given that primiparous cows have several clinical conditions, illness has an impact on lying behavior. Multiparous cows who exhibit clinical lameness tend to lie down more frequently, whereas cows that exhibit clinical lameness experience shorter and more prolonged spells. Finding and managing postpartum illnesses in pastured dairy herds can be facilitated by an understanding of these relationships.